ENHANCING CUSTOMER SATISFACTION FOR WINTERHALTER DISHWASHERS - Ryan Akmal Arisandi; Etty Nurwati; Agus Riyanto (UPT Publikasi Ilmiah UNISBA, 2024)
This study investigates the influence of product quality, after-sales service quality, and price perception on brand trust, mediated by customer satisfaction. Data was collected from 285 Winterhalter dishwasher customers using a purposive sampling method and a Likert scale questionnaire from December 2023 to February 2024. Employing Structural Equation Modeling (SEM) via SmartPLS, the analysis reveals that product quality, after-sales service quality, and price perception significantly impact customer satisfaction and brand trust, both directly and indirectly through customer satisfaction. High product quality enhances customer satisfaction and brand trust, while reliable after-sales service contributes positively to both. Competitive price perceptions that align with product value also boost satisfaction and trust. Managerially, businesses should prioritize continuous product innovation, robust after-sales services, and strategic price management to improve perceived value. These strategies are essential for achieving higher customer satisfaction and building strong brand trust, ultimately supporting sustainable growth and increased market share